2023
DOI: 10.1161/circulationaha.123.065192
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Follow-Up of Children With HLHS and Association Between Norwood Shunt Type and Long-Term Outcomes: The SVR III Study

Caren S. Goldberg,
Felicia Trachtenberg,
J. William Gaynor
et al.

Abstract: OBJECTIVE: In the SVR trial (Single Ventricle Reconstruction), newborns with hypoplastic left heart syndrome were randomly assigned to receive a modified Blalock-Taussig-Thomas shunt (mBTTS) or a right ventricle-to-pulmonary artery shunt (RVPAS) at Norwood operation. Transplant-free survival was superior in the RVPAS group at 1 year, but no longer differed by treatment group at 6 years; both treatment groups had accumulated important morbidities. In the third follow-up of this cohort (SVRIII [Long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Interestingly, the presence of a systemic-to-pulmonary shunt at stage I was a significant protective factor for RV dysfunction after stage II, which is consistent with our previous report on our extended ( n = 146) HLHS/AA cohort and with several other studies [ 15–17 ]. However, recent data from a study on HLHS teenagers ( n = 168) revealed no association between the initial shunt type at the Norwood procedure and RV function at the age of 10 years (10.4–11.5) [ 18 ]. Of note, this study did not focus on HLHS/AA types.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the presence of a systemic-to-pulmonary shunt at stage I was a significant protective factor for RV dysfunction after stage II, which is consistent with our previous report on our extended ( n = 146) HLHS/AA cohort and with several other studies [ 15–17 ]. However, recent data from a study on HLHS teenagers ( n = 168) revealed no association between the initial shunt type at the Norwood procedure and RV function at the age of 10 years (10.4–11.5) [ 18 ]. Of note, this study did not focus on HLHS/AA types.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated by the results of the Single Ventricle Reconstruction III study, these patients remain at ongoing risk for mortality and morbidity. 14 The “ideal” shunt type at Norwood remains elusive. One modifiable factor is a careful assessment of the timing of Stage II.…”
mentioning
confidence: 99%
“… 2 While TFS was higher with the RVPAS than with the mBTTS (74% vs 64%, P = 0.01) at 1 year, it did not differ at 3, 6, or, most recently, 12 years (59% vs 54%, P = 0.11). 2 , 3 The sobering fact that nearly half of the SVR cohort died or underwent heart transplantation by 12 years of age, nearly one-third in the first year of life, clearly underscores the opportunity for improvement in our care.…”
mentioning
confidence: 99%